Development of Cork-Bamboo-Latex as An Alternative Composite for Bottles Stoppers - Alice Soares Brito; Leonardo Nader Chagas; Juarez Vicente; Ana Paula Duarte Moreira; Cristiane Hess de Azevedo Meleiro; Harrison Lourenço Corrêa; Alexandre Miguel do Nascimento; Renata Nunes Oliveira (Journal of Applied Materials and Technology, 2022)
Agglomerated cork composites production has been arising as an alternative eco-friendly to cork stoppers use and attracts interest to create sustainable products and materials. A cork-bamboo-latex composite was developed by compression-molding and the interaction between three composite interfaces as well as their mechanical properties were evaluated by density measure, immersion test, FTIR, compression test, and microbial analysis aiming to produce an alternative material to wine closures. The results obtained were compared between the composite produced and the commercial agglomerated cork stoppers. It was possible to observe that the cork-bamboo-latex composite produced exhibited a good adhesion of all components and similar characteristics. However, it presented a slight increase in the density (from 0.37 g/cm3 to 0.65 g/cm3) and Young's modulus (from 0.033 MPa to 0.037 MPa) producing a stiffer material mainly due to bamboo presence. The migration of the stopper components (cork, bamboo, or latex) for the wine was not detected, as well as there was no visible interaction between wine and composite. In this work, the cork-bamboo-latex stopper fabricated presents a potential application as an alternative material to wine stoppers and stimulates the production of a sustainable material.